Project Based Interactive Multimedia Design with The STEAM Approach to Strengthening Pancasila Student Profiles in Elementary School - Devega, Lidya Septia; Buchori, Achmad; Sumarno, Sumarno (Universitas PGRI Semarang, 2024)
In producing interesting interactive multimedia based on STEM with the help of virtual reality which is really needed by elementary school students in studying human digestion material, it is hoped that it can be a solution so that students understand human digestion material which cannot be seen by the naked eye and packaged virtually to increase students' understanding both physically. critical and creative research was carried out on the development of interactive multimedia based on virtual reality for learning about human digestion in fifth grade elementary schools using the MDLC stage model. with six stages, namely concept, design, material collection, assembly, testing, and distribution. Then, the VR-based interactive multimedia product was validated by experts and continued with a posttest and user response questionnaire with the following results: Based on the results of material expert validation and media expert validation, an average of 93 and 96 was obtained so that the interactive multimedia product was suitable for use for limited testing at SDN Rejosari. Semarang, then a limited test was carried out to obtain the results of the posttest with the t test obtained results of 0% 5%, which means that the results of learning human digestion material with VR-based interactive multimedia are better than conventional learning models. Looking at the average learning achievement in the mean column, Group Statistics table, the experimental class average is 86.30, while the average of the experimental class is 86.30. the mean of the control class was 60.56. These results show that the learning outcomes of the experimental class are better than the control class. R Square value of 0.844 = 84.4%. This value means that the influence of VR-based interactive multimedia on learning achievement is 84.4%, while 15.6% of learning achievement is influenced by other variables outside of the independent variables in this research.